New records of Proconiini Stål, 1869 (Hemiptera: Cicadellidae: Cicadellinae) from Pará State, Brazil - Guimarães, Daniel L. P.; Carvalho, Adenomar N.; Teston, José A. (Entomological Communications, 2022)
We present new records of Proconiini Stål, 1869 (Hemiptera: Cicadellidae: Cicadellinae) for the Pará State, Brazil. Most specimens were collected in canopy of Tapajós National Forest. Diestostemma cavichiolii Pinto, Mejdalani & Takiya, 2017 is the most abundant species, while Diestostemma dubium Young, 1968 and Acrogonia albertoi Silva, Cavichioli, Takiya & Mejdalani, 2017 had less than five specimens collected. In addition, maps with geographical distribution of the species here studied are presented.